Strategic Recruitment and Selection Practices as a Basis for Effective Strategic Human Resource Management (SHRM): A Study in a Manufacturing Company, Koshi Province, Nepal - Pokharel, Yadav Prasad; Mahat, Dipak (Academia Journal of Research and Innovation, 2026)
Background: Strategic human resource management (SHRM) is an important element that requires strategic recruitment and selection that affect organizational performance, employee engagement, and competitiveness in the long term. When properly matched with the organizational objectives, these practices can make the employees have the skills and potential to push the strategic objectives.Methods: A descriptive study (cross-sectional) was done in a population of 50 employees of a manufacturing company in the Province of Koshi, Nepal. A 5-point Likert scale questionnaire was used to collect data, which were analyzed with SPSS which included descriptive statistics and Chi-square test to determine the relationship between variables.Results: The research has shown that recruitment and selection practices are overall well-executed, skill based, and open, which facilitated an alignment with organizational strategy. There was a remarkable gender disparity in the perception of the hiring decisions that lead to the achievement of strategic goals.Conclusion: Strategic recruiting and selection increases the capacity of the workforce, helps to make the operations effective and allows them to meet the long-term organizational objectives. Observing the differences in perception will also enhance inclusiveness and performance.Novelty: The present research can be viewed as the pilot of a more extensive future study since the strategic recruitment and selection methods among the manufacturing industry employees in Nepal were empirically demonstrated and the implementation of the SHRM principles in the emerging organizational environment was noted.